Mutation in gene coding for glucose-induced degradation-deficient protein contributes to high malate production in yeast strain No. 28 and No. 77 used for industrial brewing of sake. Issue 5 (4th March 2021) - Negoro, Hiroaki; Kotaka, Atsushi; Ishida, Hiroki
ABSTRACT: Saccharomyces cerevisiae produces organic acids including malate during alcohol fermentation. Since malate contributes to the pleasant flavor of sake, high-malate-producing yeast strain No. 28 and No. 77 have been developed by the Brewing Society of Japan. In this study, the genes responsible for the high malate phenotype in these strains were investigated. We had previously found that the deletion of components of the glucose-induced degradation-deficient (GID) complex led to high malate production in yeast. Upon examining GID protein–coding genes in yeast strain No. 28 and No. 77, a nonsense homozygous mutation of GID4 in strain No. 28 and of GID2 in strain No. 77 were identified as the cause of high malate production. Furthermore, complementary tests of these mutations indicated that the heterozygous nonsense mutation in GID2 was recessive. In contrast, the heterozygous nonsense mutation in GID4 was considered semidominant. Graphical Abstract: